Offense type and the arrest decision in cases of intimate partner violence - Durfee, Alesha (Crime & delinquency, 2016)
Although previous research has examined arrests for intimate partner violence (IPV), most of these analyses focus exclusively on physical assault and intimidation. Research on arrests for sexual assault have examined arrests for cases of stranger and/or acquaintance sexual assault, but have not included sexual IPV. Using data from the 2010 National Incident-Based Reporting System, this analysis is the first to calculate and compare arrest rates for sexual IPV, physical IPV, and intimidation. Results indicate that after controlling for other factors, police are less likely to make an arrest in cases of sexual IPV than in cases of physical IPV or intimidation. These findings are discussed in the context of the consequences of sexual assault on IPV victims.